The Implementation of a Differentiated Learning Model to Improve Student Learning Outcomes in History subject for Grade XI at SMA Negeri 19 Seram Bagian Barat - Urlialy, Gesia Mira; Rosely, Merti Seska; Kempa, Titin (Universitas Syiah Kuala, 2024)
This study aims to improve student learning outcomes through the implementation of a differentiated instruction model in History subject for Grade XI students at SMA Negeri 19 Seram Bagian Barat. Differentiated instruction is designed to meet the diverse learning needs of students based on their readiness, interests, and learning profiles. This research is a Classroom Action Research (CAR) conducted in two cycles. The subjects of this study were 30 students of Grade XI. Data collection techniques included observation, tests, and documentation. The results showed that the application of differentiated instruction significantly improved student learning outcomes. In the first cycle, student mastery reached 76 persen, which increased to 93 persen in the second cycle. The normal gain test results indicated a high level of improvement for most students, with an average g score of 1.85 Based on these findings, it can be concluded that the implementation of differentiated instruction is effective in improving student achievement in History.